The Effects of Erratic Ratings on Placebo Response and Signal Detection in the Roche Bitopertin Phase 3 Negative Symptom Studies—A Post Hoc Analysis. Issue 1 (24th August 2020) - Umbricht, Daniel; Kott, Alan; Daniel, David G
Abstract: Objective: In the current post hoc analyses, we assessed the impact of erratic ratings, a marker of questionable measurement quality, on placebo and drug response and drug-placebo separation in schizophrenia negative symptom trials. Methods: Data were obtained from three phase 3, multi-center, 24-week, randomized, double-blind, placebo-controlled trials with bitopertin in the treatment of negative symptoms of schizophrenia. Erratic ratings were operationally defined as at least one occurrence of at least a 20% change in negative symptom factor score in the opposite direction at consecutive visits. The effect of erratic ratings on placebo and drug response and drug-placebo separation was assessed by the protocol on a subject and site-level using a mixed model repeated measures analysis. Results: Placebo response was significantly increased in the presence of erratic ratings, both at the subject and site levels. Treatment response in the presence of erratic ratings was mixed and inconsistent across doses and protocols. In most cases removing data generated by subjects and sites with erratic ratings resulted in a numerical increase of drug-placebo difference favoring treatment. Additionally, in this post hoc analysis, 10 mg of bitopertin separated statistically significantly from placebo at the end of study in one of the protocols. Discussion: Erratic rating patterns appear to be consistently associated with increased response to placebo and a mixed response to treatment in the bitopertin negative symptoms trials and to have degraded drug-placebo separation. As a quality indicator, they may flag the need for enhanced quality control of affected sites in clinical trials.